Using the pig's brain acetylcholinesterase immobilized on a textile fiber to test the antidotes of nerve agent poisonings – part I - Moravcová, Ivana; Cabal, Jiří; Šandová, Jitka (Vojenské zdravotnické listy, 2012)
An integral part of the research and development of new antidotes against nerve agents (herein referred to as NAs) is the verification of their efficacy by means of in vitro tests. The purpose of these tests is to verify the ability of an antidote to protect cholinesterases from inhibition or to reactivate inhibited cholinesterases. For this purpose cholinesterases of different species and with a different degree of purification are traditionally used. Using immobilized cholinesterases proves to be new and advantageous for a number of reasons. The authors of the presented work verified the usability of Detehit detector (Oritest Praha Ltd) containing the pig’s brain acetylcholinesterase for this purpose. In this article we see the results of tests focused on verifying the effect of different reaction conditions on the activity of acetylcholinesterase, especially with regard to reproducibility of these measurements.
Keywords: Animals; Acetylcholinesterase; Chemical Warfare Agents; antidota; Sus scrofa; In Vitro Techniques; techniky in vitro; chemické bojové látky; Antidotes; mozek; Biosensing Techniques; acetylcholinesterasa; Brain; reaktivátory cholinesterasy; biosenzitivní techniky; buněčné kultury; zvířata; Cell Culture Techniques; Cholinesterase Reactivators